2016
DOI: 10.1055/s-0035-1567113
|View full text |Cite
|
Sign up to set email alerts
|

Segmentale Hautdurchblutungsreaktion während und nach Stimulation im Bereich der BWS

Abstract: Zusammenfassung Hintergrund: Physiotherapeutische Interventionen werden h?ufig auf H?he der thorakalen Wirbels?ule angewendet. Die segmentale Wirkung auf das sympathische Nervensystem nach einer Reizung der Haut und Muskulatur ist bislang unklar. Ziel: Das Ziel war die Evaluation (1) der Machbarkeit?und (2) der Effekte der segmentalen Perfusion?und Erythembildung nach Massage, Mobilisation, Manipulation und Placebotherapie auf H?he der thorakalen Wirbels?ule, um daraus Studiendesigns zu kreieren und erste m?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Group 1: During session 1 (day one) and in prone position, a grade 3 oscillatory mobilization in a rhythmical fashion (120 movements per minute) [27] of the thoracic spine with PAM was applied for 100 s on every thoracic segment, from T6 to T12. A wash-out phase of at least 24 h was guaranteed [19, 20]. During session 2 (day two) and in sitting position, a grade 3 oscillatory mobilization in a rhythmical fashion (120 movements per minute) but now with anterior-posterior mobilization (APM) was applied for 100 s on every thoracic segment from T6 to T12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1: During session 1 (day one) and in prone position, a grade 3 oscillatory mobilization in a rhythmical fashion (120 movements per minute) [27] of the thoracic spine with PAM was applied for 100 s on every thoracic segment, from T6 to T12. A wash-out phase of at least 24 h was guaranteed [19, 20]. During session 2 (day two) and in sitting position, a grade 3 oscillatory mobilization in a rhythmical fashion (120 movements per minute) but now with anterior-posterior mobilization (APM) was applied for 100 s on every thoracic segment from T6 to T12.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, there is little empirical evidence on the effects of thoracic spine mobilization (TSM) on SPB. There are currently three studies that have investigated the effects of TSM on the SPB [11, 19, 20]. A single case study [21] observed that TSM in a young male volunteer resulted in a decreased skin perfusion and erythema in the thoracic segment, suggesting an acute increase of SNS activity.…”
Section: Introductionmentioning
confidence: 99%
“…Navarro-Santana et al [55] postulierten, dass Wirbelsäulenmobilisationen unabhängig von der Behandlungsregion eine Aktivitätserhöhung des SyNS hervorrufen (Zielparameter: Hautleitfähigkeit-und temperatur). Bialosky et al [56] und Rogan et al [57,58] stellten ein neurophysiologisches Modell vor, welches interagierende Bahnen des peripheren und zentralen Nervensystems einschließt, die den Effekt von MTTe erklären. Realisierte Studien [59,60,61] zur Entschlüsselung neuronaler Bahnen im Gehirn weisen nach, dass Zwischen-und Mittelhirn nach starker Stimulation eine zentrale Rolle spielen bei der Aktivierung der Herz-und Atemfrequenz, dem Blutdruck sowie der Körpertemperatur.…”
Section: Rolle Der Behandlungsregionunclassified